A Guide for Cortical Electrical Stimulation Mapping. Issue 2 (March 2018) - So, Elson L.; Alwaki, Abdulrahman
Abstract : Summary: Electrical stimulation mapping (ESM) of the brain remains a major procedure for guiding epilepsy and tumor surgeries. This article collates available experiences and data in ESM to develop a guide for conducting the procedure. There are many factors that influence the yield of ESM. The stimulation parameters offered in this article need to be adjusted within safe limits to address the factors. Each ESM procedure should be tailored to the patient's age and baseline mental or psychological capacity. Stimulation-induced seizures and EEG afterdischarges disrupt ESM procedure and render the interpretation of the results difficult. There are specific measures that can lessen the risk of seizures and afterdischarges during ESM. Electrical stimulation mapping procedure requires several tasks on the part of those conducting the procedure, such as operating the stimulator and the EEG recording equipment, administering behavioral or language tests and observing both patient and EEG responses to the stimulation. A team of experienced staff is necessary for individual assumption of each task. Knowledge of the spatial relationship between electrode contacts and underlying normal or abnormal brain structures is essential for interpreting ESM results. When testing for motor or sensory response, be aware of the distinction between responses at the primary motor area and responses at the supplementary sensorimotor area. The anatomy of supplementary sensorimotor area is more variable and functional than it is fixed and structural, although its general confines and somatotopic organization are known. In addition, negative motor responses to stimulation must be recognized to avoid misinterpretation of ESM results, especially in language mapping.